Albert Watkins and Howard Watkins Family Genealogy Trip to Tennessee - Watkins, Howard::::::::: (1986)
Pauline Gibson Shoemaker and Albert Watkins viewing just a part of Henry Luis Watkins' large farm The red rental car was used by Albert and Howard to visit relatives and tour sites.